Tal Lovejoy - unknown:::Creator::::::::::::
Tal Lovejoy standing on the beach in Alaska. Tal (Natalya) was part of the discussion group that gathered at Ed Ricketts lab. Text imprint reads " YOUR NEWSREEL REPORTING SQUEEKING."